The developmental biogeography of hawksbill sea turtles in the North Pacific. Issue 8 (8th March 2016) - Van Houtan, Kyle S.; Francke, Devon L.; Alessi, Sarah; Jones, T. Todd; Martin, Summer L.; Kurpita, Lauren; King, Cheryl S.; Baird, Robin W.
Abstract: High seas oceanic ecosystems are considered important habitat for juvenile sea turtles, yet much remains cryptic about this important life‐history period. Recent progress on climate and fishery impacts in these so‐called lost years is promising, but the developmental biogeography of hawksbill sea turtles ( Eretmochelys imbricata ) has not been widely described in the Pacific Ocean. This knowledge gap limits the effectiveness of conservation management for this globally endangered species. We address this with 30 years of stranding observations, 20 years of bycatch records, and recent simulations of natal dispersal trajectories in the Hawaiian Archipelago. We synthesize the analyses of these data in the context of direct empirical observations, anecdotal sightings, and historical commercial harvests from the insular Pacific. We find hawksbills 0–4 years of age, measuring 8–34 cm straight carapace length, are found predominantly in the coastal pelagic waters of Hawaii. Unlike other species, we find no direct evidence of a prolonged presence in oceanic habitats, yet satellite tracks of passive drifters (simulating natal dispersal) and our small sample sizes suggest that an oceanic phase for hawksbills cannot be dismissed. Importantly, despite over 600 million hooks deployed and nearly 6000 turtle interactions, longline fisheries have never recorded a single hawksbill take. We address whether the patterns we observe are due to population size and gear selectivity. Although most sea turtle species demonstrate clear patterns of oceanic development, hawksbills in the North Pacific may by contrast occupy a variety of ecosystems including coastal pelagic waters and shallow reefs in remote atolls. This focuses attention on hazards in these ecosystems – entanglement and ingestion of marine debris – and perhaps away from longline bycatch and decadal climate regimes that affect sea turtle development in oceanic regions. Abstract : Though most sea turtle species demonstrate clear patterns of oceanic development, hawksbills in the North Pacific may by contrast occupy a variety of ecosystems including coastal pelagic waters and shallow reefs in remote atolls. This focuses attention on hazards in these ecosystems – entanglement and ingestion of marine debris – perhaps away from longline bycatch and decadal climate regimes that affect sea turtle development in oceanic regions.